The influence of polymeric charge and structure, molecular weight and ionic conditions on depressant ability to reduce the natural floatability of talc - Shortridge, Paul Graham (Department of Chemical Engineering, 2023)
Talc is a naturally floatable gangue material common in South African platinum bearing (PGM) ore bodies. Long chain polysaccharide depressants are effective in depressing talc flotation and improving the grade of the concentrates of those ores with talc as a gangue constituent. This thesis describes an investigation into the surface interactions of two types of long chain polysaccharide depressants (carboxymethylcellulose and guar gum) with pure talc and with Merensky PGM ore (which is known to contain talc as a gangue constituent). Specifically, the objectives of this thesis were as follows: 1. To characterize the differences in the depressants selected. 2. To examine the effects that polymeric structure and molecular weight of the depressant have on the hydrophobicity of talc. 3. To extrapolate the findings from highly controlled laboratory conditions to batch flotation tests with Merensky PGM ore. During the course of the experiments, it became clear that ionic conditions were an important factor in this system and they were therefore incorporated into the work done. Overall, the molecular weight of the depressants was not seen to be an important factor in their ability to depress talc. The molecular structure did appear to impact depressant efficiency, but only under conditions oflow ionic strength in the microflotation system. III Ionic conditions were found to be a pivotal factor in the performance of the CMC depressants in reducing the flotation of talc. It was also found that the ions adsorbed onto the talc surface in the absence of depressants - leading to a reduction in talc floatability. Divalent cations were more effective than monovalent cations in enhancing the effectiveness of the CMC depressants - suggesting stronger adsorption under these conditions. Guar depressants appeared to be unaffected by varying ionic conditions. The batch flotation tests, and the microflotation tests at the higher ionic strengths, showed that similar depressing ability was obtained for the CMCs and the guars. However, the batch floats indicated that increasing dosage led to improved depressant performance while the microflotation tests indicated that a maximum level of depression was achieved at fairly low dosages